KAJIAN MACAM MULSA TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI (Glycine max (L.) Merrill) - Priyono, Iksan; Santosa, Sartono Joko; Sumarmi, Sumarmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2021)
The study of mulch on the growth and yield of three varieties of Soybean (Glycine Max (L.) Merrill)